Optimal self‐healing strategy for microgrid islanding. Issue 4 (23rd October 2018) - Sun, Wei; Ma, Shanshan; Alvarez‐Fernandez, Inalvis; Roofegari nejad, Reza; Golshani, Amir
Abstract : Renewable resource based microgrids provide reliable and cost‐effective electricity with low carbon emissions. The flexibility of operating in grid‐connected or islanded modes enables a microgrid to serve loads reliably. In the case of unexpected events happening to the main grid, the microgrid will isolate itself and operate in islanded mode to prevent any adversary impacts. The availability of renewable generation in the microgrid has significant impacts on the islanding strategy and different scenarios need to be considered. This study proposes a comprehensive microgrid self‐healing strategy under different circumstances. The proposed strategy encompasses generation re‐dispatch, network reconfiguration, and load shedding. The microgrid self‐healing problem is formulated as a mixed‐integer quadratic programming problem, which provides a globally optimal solution to facilitate smooth islanding of the microgrid. A modified Consortium for Electric Reliability Technology Solutions microgrid is used to conduct simulation under various scenarios. The simulation results demonstrate the efficiency of the proposed self‐healing strategy in minimising costs of load shedding and generation with optimal switching actions.